2018
DOI: 10.1016/j.neuropharm.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Depolarizing, inhibitory GABA type A receptor activity regulates GABAergic synapse plasticity via ERK and BDNF signaling

Abstract: γ-aminobutyric acid (GABA) begins as the key excitatory neurotransmitter in newly forming circuits, with chloride efflux from GABA type A receptors (GABARs) producing membrane depolarization, which promotes calcium entry, dendritic outgrowth and synaptogenesis. As development proceeds, GABAergic signaling switches to inhibitory hyperpolarizing neurotransmission. Despite the evidence of impaired GABAergic neurotransmission in neurodevelopmental disorders, little is understood on how agonist-dependent GABAR acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 71 publications
2
38
0
Order By: Relevance
“…Phosphorylation of gephyrin at Ser270 is mediated by CDK5 and GSK3β, while a partnering and functionally relevant Ser268 site is regulated by ERK1/2 (31). While the exact signaling mechanism responsible for gephyrin remodeling and phosphorylation in our study is unclear, we have previously shown 30 min treatment with the GABA A R agonist muscimol leads to ERK1/2/BDNF signaling, decreased gephyrin synaptic and total levels, and decreased γ2-GABA A R at synapses and potentiation by BZDs (55). Thus, changes in receptor and scaffold synaptic level and function can occur on the timescale of minutes.…”
Section: Discussionmentioning
confidence: 55%
“…Phosphorylation of gephyrin at Ser270 is mediated by CDK5 and GSK3β, while a partnering and functionally relevant Ser268 site is regulated by ERK1/2 (31). While the exact signaling mechanism responsible for gephyrin remodeling and phosphorylation in our study is unclear, we have previously shown 30 min treatment with the GABA A R agonist muscimol leads to ERK1/2/BDNF signaling, decreased gephyrin synaptic and total levels, and decreased γ2-GABA A R at synapses and potentiation by BZDs (55). Thus, changes in receptor and scaffold synaptic level and function can occur on the timescale of minutes.…”
Section: Discussionmentioning
confidence: 55%
“…The SNPs of the TrkB gene were associated with the emotional arousal or the impulsivity phenotypes in healthy people [18,23]. It was found that the BDNF-TrkB signaling affects the plasticity mechanisms at the GABAergic synapses [10]. In schizophrenia, several alterations were revealed in GABA neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that this receptor might prompt the synthesis of gamma amino butyric acid (GABA) and the expression of the glutamate receptors. Additionally, schizophrenia is connected with a dysfunction of the GABA neurotransmission [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies of agonist-dependent plasticity at inhibitory synapses have suggested the involvement of underlying mechanisms that require depolarising currents mediated by GABAARs to induce Ca 2+ signalling 29,45 . These studies have associated depolarising GABAcurrents with reduced synaptic efficacy.…”
Section: Direction Of Gaba Clflux and Iltpmentioning
confidence: 99%
“…Nevertheless, many studies have focused on changes to the receptor following sustained activation with agonists or allosteric modulators 17 . These changes include: phosphorylation of receptor subunits [18][19][20][21] , altered expression of GABAARs 18,21-28 , changes to receptor mobility and clustering 26,[29][30][31] , and alterations to receptor pharmacology 32 .…”
Section: Introductionmentioning
confidence: 99%